1965
DOI: 10.1038/bjc.1965.34
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Chemical Induction of Hyperplasia and of Malignancy in the Bladder Epithelium

Abstract: 4-ETHYLSULPHONYLNAPHTHALENE-1 -SULPHONAMIDE (HPA) induces hyperplasia of the bladder epithelium in the rat and mouse (Paget, 1958;Sen Gupta, 1962). The hyperplasia arises within forty-eight hours of the first administration of the chemical (Bonser and Clayson, 1964) and with repeated dosing is still present after forty weeks (Sen Gupta, 1962). Carcinomas of the bladder were found in Ab x IF mice receiving the chemical for up to sixty-five weeks and were more prevalent in female than in male mice (Bonser and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1966
1966
2004
2004

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…As for the possible carcinogenic effect of cyclophosphamide on bladder epithelium [11], this does not seem likely in mice considering the assump tion by Clayson et al [5] that a correlation exists between early hyper plasia and the ultimate development of malignancy. On the other hand, while T okuoka [19] has reported a higher incidence of tumours in mice following repeated injections of cyclophosphamide, no bladder tumour has been detected and this drug has not resulted in a bladder carcinogen in C57 x IF mice, either alone or associated to paraffin wax-pellet im plantation [3].…”
Section: Discussionmentioning
confidence: 99%
“…As for the possible carcinogenic effect of cyclophosphamide on bladder epithelium [11], this does not seem likely in mice considering the assump tion by Clayson et al [5] that a correlation exists between early hyper plasia and the ultimate development of malignancy. On the other hand, while T okuoka [19] has reported a higher incidence of tumours in mice following repeated injections of cyclophosphamide, no bladder tumour has been detected and this drug has not resulted in a bladder carcinogen in C57 x IF mice, either alone or associated to paraffin wax-pellet im plantation [3].…”
Section: Discussionmentioning
confidence: 99%
“…Such a mechanism is made more probable by the demonstration by Walker (1959) that wounding the bladder epithelium of the mouse with a pointed scalpel blade is followed by a wave of mitotic activity from one to four days thereafter. In other, unpublished, observations it has been found that the hyperplasia induced by the oral administration of chemical bladder carcinogens (Clayson et al, 1965) is also associated with an increase in the number of mitoses in the epithelium.…”
Section: Discussionmentioning
confidence: 83%
“…implicated as a relevant factor in the induction of cancer of the bladder of mice given chemicals by mouth (Clayson, Lawson, Santana and Bonser, 1965). The technique of bladder implantation has been used to test chemicals for local carcinogenic action (Jull, 1951;Allen, Boyland, Dukes, Horning and Watson, 1957).…”
mentioning
confidence: 99%
“…It is possible that the A x IF mice are intrinsically less sensitive to ENS but, alternatively, the low incidence of bladder tumours may be a result of the condition of many of the mice during the experiment. This opinion is reinforced by the fact that the Ab x IF mice used by Clayson and Bonser (1965) developed a higher incidence of bladder tumours despite the Ab parents being derived by Caeserian section from an A mouse of the line used in this experiment.…”
Section: Discussionmentioning
confidence: 93%
“…Bladder tumours result from prolonged feeding of ENS to mice (Clayson and Bonser, 1965;Clayson, Pringle and Bonser, 1967). Hyperplasia is more severe and tumcours are more frequent in female than in male mice.…”
mentioning
confidence: 99%